LINGUISTIC INTELLIGENCE AS A DRIVING FORCE FOR WRITING CREATIVITY OF JUNIOR HIGH SCHOOL STUDENTS IN MAKASSAR - Juanda, juanda; Saraswati; Johar Amir (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
Writing can be an effective tool for student learning and development, particularly when used as a project-based approach that allows for the practical application of classroom knowledge. The research has three objectives, namely to describe: linguistic intelligence of Makassar City junior high school students; students' fantasy story writing skills; and prove the influence of linguistic intelligence on students' fantasy story writing skills. This research is categorized as quantitative research. Data collection in this study used tests, namely a test of students' linguistic intelligence knowledge and a product test in the form of writing fantasy stories. The finding of the research is that there is an influence of linguistic intelligence on the fantasy story writing skills of Makassar City junior high school students. The results of simple linear regression calculations show that the t-test result (12.012) > t table (1.652) with a significance of 0.00 <0.05 therefore, the t-test result (12.012) > t table (1.652) means H0 is rejected and Ha is accepted. The conclusion is that linguistic intelligence affects students' fantasy story writing skills. The contribution of this research is to provide new knowledge to students and teachers that linguistic or good language intelligence can produce good writing. Future research will explore more intelligence other than linguistic intelligence possessed by students.